An audit of gynae-oncology practices in ovarian cancer treatment based on enhanced recovery after surgery (ERAS) protocol amongst two gynae-oncology units, in UK and in Pakistan - Uzma Chishti; Munazza Akhtar; Aliya Aziz; Amber Ahmed; Desmond PJ Barton (Journal of the Pakistan Medical Association, 2021)
Objectives: The goal of this study was to compare the peri-operative practices and complications in ovarian cancer patients undergoing upfront surgery for primary disease at two centers; in UK following ERAS protocol and in Pakistan following traditional practices. Methodology: This was a cross-sectional study based in Gynecology departments of St. Georges Hospital UK, and Aga Khan Hospital Pakistan. The study population consisted of 50 patients from each centre, from January 2015 till December 2016. Results: Demographics were comparable except more prevalent diabetes in Pakistan. Pakistani patients had bowel preparation in 94% as compared to two percent in UK. Duration for nil per mouth was more in traditional approach as well as the use of nasogastric tube and peritoneal drain (0.0001). Epidural anesthesia was used in 78% of patients in Pakistan compared to only 8% in UK. The duration of thromboprophylaxis was also significantly different (UK 28 days versus Pakistan 7 days). Electrolyte imbalances was detected in 80% of Pakistani and 15% of UK patients. Wound infection recorded in 15% of UK and 2% of Pakistani patients. The median length of hospital stay was 7 and 8 days in ERAS and non-ERAS patients respectively. Conclusion: Implementation of ERAS protocol can lead to improvement of postoperative outcomes and good functional recovery without compromising patient safety. Continuous...